3D Printed Integrated Multi-Layer Microfluidic Chips for Ultra-High Volumetric Throughput Nanoliposome Preparation - Shan, Han; Lin, Qibo; Wang, Danfeng; Sun, Xin; Quan, Biao; Chen, Xiang; Chen, Zeyu (Frontiers in Bioengineering and Biotechnology, 2021)
Although microﬂuidic approaches for liposomes preparation have been developed, fabricating microfluidic devices remains expensive and time-consuming. Also, owing to the traditional layout of microchannels, the volumetric throughput of microfluidics has been greatly limited. Herein an ultra-high volumetric throughput nanoliposome preparation method using 3D printed microfluidic chips is presented. A high-resolution projection micro stereolithography (PμSL) 3D printer is applied to produce microfluidic chips with critical dimensions of 400 µm. The microchannels of the microfluidic chip adopt a three-layer layout, achieving the total flow rate (TFR) up to 474 mL min−1, which is remarkably higher than those in the reported literature. The liposome size can be as small as 80 nm. The state of flows in microchannels and the effect of turbulence on liposome formation are explored. The experimental results demonstrate that the 3D printed integrated microfluidic chip enables ultra-high volumetric throughput nanoliposome preparation and can control size efficiently, which has great potential in targeting drug delivery systems.